2016
DOI: 10.1186/s12889-016-3882-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in the prevalence of non-communicable diseases risk factors among 25–74 years old citizens in Yangon Region, Myanmar: a cross sectional study

Abstract: BackgroundRecent societal and political reforms in Myanmar may upturn the socio-economy and, thus, contribute to the country’s health transition. Baseline data on urban-rural disparities in non-communicable disease (NCD) risk factors are not thoroughly described in this country which has been relatively closed for more than five decades. We aim to investigate urban-rural differences in mean values and the prevalence of selected behavioral and metabolic risk factors for non-communicable diseases and 10-years ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
55
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 35 publications
14
55
3
Order By: Relevance
“…The low physical activity was associated with overweight and obesity [52]. This finding is consistent with studies done in Myanmar, Malaysia, and the United States [53][54][55]. Working environments should promote physical activity and integrating enough public spaces for physical exercise should be considered in urban development and planning.…”
Section: Discussionsupporting
confidence: 84%
“…The low physical activity was associated with overweight and obesity [52]. This finding is consistent with studies done in Myanmar, Malaysia, and the United States [53][54][55]. Working environments should promote physical activity and integrating enough public spaces for physical exercise should be considered in urban development and planning.…”
Section: Discussionsupporting
confidence: 84%
“…19,20 Our study showed that people living in urban areas of Vietnam are more likely to consume more alcohol, have a higher BMI, and have been diagnosed with diabetes more when compared to those in rural areas. The result is in alignment with the studies of NCD behavioral risk factors between urban and rural dwellers in other lower-and middle-income countries in Asia such as Myanmar, 21 and Cambodia, 22 as well as in other countries from different geographical area such as Africa: the Zulu community, Uganda, and Cameroon, [23][24][25] where rural-urban disparities persist.…”
Section: Discussionsupporting
confidence: 77%
“…It was also found that the smoking rate was lower than the rates in literature both in Turkey and the world, and the prevalence rates of diabetes and obesity were higher than the rates in literature both in Turkey and the world. In addition, it was founded that the cancer screening rates were higher when compared with the studies done in Turkey in the past, but lower in comparison with those of developed countries (15,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of circulatory system diseases was found to be 25.6% in rural areas and 21.7% in urban areas (23). In the study by Htet et al, it was determined that the prevalence of behavioral risk factors in individuals living in rural areas for NCD was higher than that in those living in urban areas (21). In this study, because more than half of the participants had a chronic disease, health personnel working at FHCs in rural areas have important responsibility.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation